Post-fire transformation of basic components of pine forests in Central Siberia - G. A. Ivanova; S. V. Zhila; V. A. Ivanov; N. M. Kovaleva; E. A. Kukavskaya (Сибирский лесной журнал, 2018)
Based on experiments of forest fire modeling conducted in 2000–2003 for the first time in Siberia, long-term monitoring of impact of various intensities fires on Scots pine stand components and post-fire succession was conducted. The most significant postfire transformation of all Scots pine stands components was revealed after high-intensity fires. The relationship between tree mortality and fire intensity was established. The estimation of initial post-fire succession, change of composition and structure of grasses and small shrubs as well as pine regeneration was provided. The relationship between phytomass consumption and fire intensity was established. Aboveground phytomass decreased after fires of low intensity by 5–10 %, and after high-intensity fires – by 74 %. The greatest accumulation of ground phytomass occurs in the first postfire years, which is associated with the intensive tree mortality during this period. Due to tree mortality, mortmass (duff, down woody debris) increased after high-intensity fire more than two times. After the fires, the redistribution of the living biomass to mortmass occurs, with highest changes found after high-intensity fires. The relationships between phytomass accumulation and fire intensity and time since fire were obtained for southern and central taiga Scots pine stands. The investigation conducted allows to forecast impact of fires of various intensities on forest components, post-fire succession and reforestation of Siberian Scots pine stands based on data on prefire pine characteristics and fire intensity.